Financial Analysis for the Implementation of an Urban Electric Bus in the City of Cuenca - Torres-Moscoso, Diego Francisco (2022)
The present paper carried out a financial analysis that allows establishing the economic feasibility of implementing electric buses for urban service in the city of Cuenca, which circulate through urban routes that connect the main university campuses of the city, which is located at 2 560 meters above sea level and has an urban population of 329 928 inhabitants; for this purpose, five urban routes were established that allow the connection between the universities, proposing routes with lengths of 14 to 34 km, with a duration of 30 minutes to one hour and fifteen minutes, considering the mobilization of 40 000 students. The costs of analysis include income, which implies the value of the ticket and mobile advertising, on the other hand, there are the expenses, such as the acquisition of the unit, maintenance and spare parts, financing and operating expenses; once the values are determined, net present value (NPV) and internal rate of return (IRR) conditions are applied. As a result, lower and negative values are obtained, resulting in an unprofitable project, and this is due to the $ 0.31 ticket value; as a conclusion and in order for the project to be profitable, a 61 to 83 % increase in the ticket is considered.